THE ROLE OF DIGITAL MARKETING PLATFORMS ON SUPPLY CHAIN MANAGEMENT FOR CUSTOMER SATISFACTION AND LOYALTY IN SMALL AND MEDIUM ENTERPRISES (SMES) AT INDONESIA - Adam, Muhammad; Ibrahim, Mahdani; Ikramuddin, Ikramuddin; Syahputra, Hendra (International Journal of Supply Chain Management, 2020)
Abstract. The main aim is to investigate the digital technologies supporting small and medium enterprises (SMEs) operating in creative industries in their supply chain management strategies. In the globalization era, digital marketing platforms play a significant role in increasing customer loyalty and indirectly effect on the economic growth of a community. In conjunction with its essential issue, the current study aims to investigate the role of digital marketing platforms (online media) and its structural relationship to the consumer satisfaction and loyalty in SMEs at Aceh province, Indonesia. This study designed using Quantitative analysis with a cross-sectional study through a survey questionnaire. This study involved all of the customers the SMEs products in Aceh province, Indonesia. A total of 219 customers have participated in answering the survey questionnaire via Google forms. The data analyzed using the Analysis of Moments Structure by assisting the statistical software IBM - AMOS Version 22. The digital platforms performed by using the Sobel test. The results of this study found that the digital marketing for supply chain (online media) significantly affect consumer satisfaction. Then, digital supply chain has a significant effect on consumer satisfaction. Also, this study found that the product review does not significantly affect the consumer loyalty. Besides that, the consumer satisfaction and the use of online media directly affect the consumer loyalty. In conclusions, this study successfully investigated the online media digital supply chain, and consumer satisfaction and its structural relationship on consumer loyalty in SMEs products that viewed as a digital marketing perspective. Then, this study comprehensively evaluated the role of digital supply chain, consumer satisfaction, and consumer loyalty in providing SME products with competitive advantages that contribute to regional economic growth. Supply chain management practices were also statistically significant, and mediated the relationship between customer satisfaction and product quality and flexibility